Mathematics Exam  >  Mathematics Questions  >  General solution of pde given below is (y2+ z... Start Learning for Free
General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0
  • a)
  • b)
  • c)
  • d)
Correct answer is option 'A'. Can you explain this answer?
Verified Answer
General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0...
ANSWER :- a
Solution :- Lagrange auxiliary equations are :-
dx/(y^2 + z^2 - x^2) = -dy/(-2xy) = -dz/(2xz)
Taking the last two members, we get
dy/y = dz/z
Integrating log y = logz + logc1
=y/z = c1
Using ,multipliers x,y,z we get (xdx + ydy + zdz)/-x(x^2 + y^2 + z^2) 
(xdx + ydy + zdz)/-x(x^2 + y^2 + z^2) = dx/(-2xz)
2(xdx + ydy + zdz)/(x^2 + y^2 + z^2) = dz/z
Integrating, log(x^2 + y^2 + z^2) = logz + logc2
(x^2 + y^2 + z^2) = zc2
Hence the required solution is f(c1,c2) = 0
= f(y/z, (x^2 + y^2 + z^2)/z) = 0
View all questions of this test
Most Upvoted Answer
General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0...
ANSWER :- a
Solution :- Lagrange auxiliary equations are :-
dx/(y^2 + z^2 - x^2) = -dy/(-2xy) = -dz/(2xz)
Taking the last two members, we get
dy/y = dz/z
Integrating log y = logz + logc1
=y/z = c1
Using ,multipliers x,y,z we get (xdx + ydy + zdz)/-x(x^2 + y^2 + z^2) 
(xdx + ydy + zdz)/-x(x^2 + y^2 + z^2) = dx/(-2xz)
2(xdx + ydy + zdz)/(x^2 + y^2 + z^2) = dz/z
Integrating, log(x^2 + y^2 + z^2) = logz + logc2
(x^2 + y^2 + z^2) = zc2
Hence the required solution is f(c1,c2) = 0
= f(y/z, (x^2 + y^2 + z^2)/z) = 0
Free Test
Community Answer
General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0...
ANSWER :- a
Solution :- Lagrange auxiliary equations are :-
dx/(y^2 + z^2 - x^2) = -dy/(-2xy) = -dz/(2xz)
Taking the last two members, we get
dy/y = dz/z
Integrating log y = logz + logc1
=y/z = c1
Using ,multipliers x,y,z we get (xdx + ydy + zdz)/-x(x^2 + y^2 + z^2) 
(xdx + ydy + zdz)/-x(x^2 + y^2 + z^2) = dx/(-2xz)
2(xdx + ydy + zdz)/(x^2 + y^2 + z^2) = dz/z
Integrating, log(x^2 + y^2 + z^2) = logz + logc2
(x^2 + y^2 + z^2) = zc2
Hence the required solution is f(c1,c2) = 0
= f(y/z, (x^2 + y^2 + z^2)/z) = 0
Explore Courses for Mathematics exam
Question Description
General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? for Mathematics 2025 is part of Mathematics preparation. The Question and answers have been prepared according to the Mathematics exam syllabus. Information about General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? covers all topics & solutions for Mathematics 2025 Exam. Find important definitions, questions, meanings, examples, exercises and tests below for General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer?.
Solutions for General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? in English & in Hindi are available as part of our courses for Mathematics. Download more important topics, notes, lectures and mock test series for Mathematics Exam by signing up for free.
Here you can find the meaning of General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? defined & explained in the simplest way possible. Besides giving the explanation of General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer?, a detailed solution for General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? has been provided alongside types of General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? theory, EduRev gives you an ample number of questions to practice General solution of pde given below is (y2+ z2+ x2 )p - 2xyq + 2xz = 0a)b)c)d)Correct answer is option 'A'. Can you explain this answer? tests, examples and also practice Mathematics tests.
Explore Courses for Mathematics exam
Signup to solve all Doubts
Signup to see your scores go up within 7 days! Learn & Practice with 1000+ FREE Notes, Videos & Tests.
10M+ students study on EduRev